Changes in labour market conditions and policies: Their impact on wage inequality during the last decade - Saúl N. Keifman; Roxana Maurizio (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Labour market incomes have been a major contributor to the important fall in inequality in Latin America during the 2000s. Indeed, it was the main contributor in countries where inequality fell more dramatically. A proper understanding of the workings of the labour market is necessary to comprehend why inequality fell, what lies ahead of us and what we can do to achieve more equitable societies in Latin America. Social progress was real in the last decade but we should not overlook the structural deficits that still remain in Latin American labour markets. Inequality fell more dramatically in countries where formality rose faster and real minimum wages increased more significantly. Labour market institutions have a played positive role in reducing inequity in the last decade.
Keywords: J5; J81; D3; D36; 330; labour institutions; inequality; Latin America; minimum wage; Arbeitsmarkt; Arbeitsmarktpolitik; Mindestlohn; Lateinamerika